A wide‐necked extracranial internal carotid artery saccular aneurysm with ipsilateral proximal compression. Issue 2 (5th August 2016) - Jin, ChunXiang; Hu, ZhenZhen; He, Yu
ABSTRACT: Extracranial internal carotid artery aneurysms (EICAA) are rare and can elicit various neurologic symptoms. Here, we present a case of a saccular EICAA compressing its proximal parent internal carotid artery (ICA). Ultrasonography demonstrated the proximal ICA stenosis and the "tardus‐parvus" Doppler waveform downstream. The patient underwent aneurysmectomy and graft interposition. The histologic analysis highly supported an atypical fibromuscular dysplasia. Although this patient only showed a neck mass, the reduced ipsilateral cerebral blood supply was a potential cause for neurologic symptoms. © 2016 Wiley Periodicals, Inc. J Clin Ultrasound 45 :116–120, 2017;